The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/fst.38818
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of tanshinone IIA from Salvia miltiorrhiza Bge on human bladder cancer BIU-87 cells and xenograft in nude mice

Abstract: The objective of this study was to investigate the inhibitory effects of tanshinone OOA on human bladder cancer BOU-87 cells and the xenograft in nude mice. BOU-87 cells were treated with tanshinone OOA with concentration of 0.5, 1, 2 and 4 g/L. The cell proliferation, cycle and apoptosis were detected. The nude mice with BOU-87 cell xenograft were treated with normal saline (control), 5-fluorouracil (5-FU), 200, 400 and 600 mg/kg tanshinone OOA, respectively. The animal body weight and growth of tumor were me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Studies have found that many plants contain the ingredients which have good activities in antioxidant, anti-inflammatory, anti-tumor and other aspects (Costa et al, 2020;Huang et al, 2020;Santos et al, 2021). Curcumol is a sesquiterpene compound isolated from the zedoary turmeric oil which has long been used as a folk medicine in China for many years (You et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have found that many plants contain the ingredients which have good activities in antioxidant, anti-inflammatory, anti-tumor and other aspects (Costa et al, 2020;Huang et al, 2020;Santos et al, 2021). Curcumol is a sesquiterpene compound isolated from the zedoary turmeric oil which has long been used as a folk medicine in China for many years (You et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Tanshinone in S. miltiorrhiza has definite curative effect on cardiovascular diseases and neurological diseases (Hao et al, 2015;Xu et al, 2021). Recently, tanshinone has been found to have an inhibitory effect on human bladder cancer cells (Huang et al, 2020). In addition, Gengmao et al (2014) found that the adaptive response to salt stress in S. miltiorrhiza was linked with its highly induced antioxidant enzyme defense systems.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Lachnospiraceae is a highly abundant bacterial family within the gut microbiota in human, whose members may protect against human colon cancer by producing butyric acid, a substance that is important for both microbial and host epithelial cell growth (Meehan & Beiko, 2014;Yang et al, 2020;Huang et al, 2020;Hwang et al, 2019;Grom et al, 2020). In this study, the compositions of Lachnospiraceae in the control, lowdose, medium-dose and high-dose groups were 34.1%, 36.9%, 32.84% and 31.39%, respectively.…”
Section: Discussionmentioning
confidence: 99%